2023
DOI: 10.3390/ijms241310796
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Biomarkers of Plasma Trimethylamine N-Oxide and Short-Chain Fatty Acids for Recanalization Therapy in Acute Ischemic Stroke

Abstract: Bidirectional communication of the microbiota–gut–brain axis is crucial in stroke. Recanalization therapy, namely intravenous thrombolysis (IVT) and endovascular thrombectomy (EVT), are recommended for eligible patients with acute ischemic stroke (AIS). It remains unclear whether gut microbiota metabolites, namely trimethylamine N-oxide (TMAO) and short-chain fatty acids (SCFAs), can predict the prognosis after recanalization therapy. This prospective study recruited patients with AIS receiving IVT, EVT, or bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Notably, isovalerate was found to be associated with the BMB outcome. A previous study has revealed that elevated plasma levels of isovalerate, a branched short-chain fatty acid, were observed following acute AIS reperfusion therapy, correlating with the severity and disability of stroke [63]. In another casecontrol study, elevated levels of linoleic acid were noted in patients with hemorrhagic stroke [64].…”
Section: Discussionmentioning
confidence: 94%
“…Notably, isovalerate was found to be associated with the BMB outcome. A previous study has revealed that elevated plasma levels of isovalerate, a branched short-chain fatty acid, were observed following acute AIS reperfusion therapy, correlating with the severity and disability of stroke [63]. In another casecontrol study, elevated levels of linoleic acid were noted in patients with hemorrhagic stroke [64].…”
Section: Discussionmentioning
confidence: 94%
“…41 However, a 2023 prospective study revealed no association between TMAO levels and ischemic stroke severity or functional prognosis following reperfusion therapy. 86…”
Section: Potential Value Of Tmaomentioning
confidence: 99%
“…Moreover, a 2023 study found that elevated plasma isovaleric acid levels were negatively correlated with the severity of mild stroke and disability postreperfusion therapy for ischemic stroke. 86 Collectively, these clinical studies imply that SCFA supplementation could be beneficial for treating ischemic stroke and enhancing prognosis.…”
Section: Human Studiesmentioning
confidence: 99%
“…The GM in uences stroke risk through various pathways, including host metabolism, immune responses, and vascular function. For instance, GM impact the production of metabolites such as short-chain fatty acids (SCFA) and trimethylamine N-oxide (TMAO), directly linked to stroke incidence [9][10][11]. However, observational studies have limitations, often overlooking key confounding factors, leading to biased results [12].…”
Section: Introductionmentioning
confidence: 99%